Compression-resistant and torsion-resistant energy storage cable and preparation method thereof
By using a compressive outer shield and lubricating shield layer composed of high-density polyethylene and other materials on the energy storage cable, the problem of insufficient compressive and torsion resistance of energy storage cables is solved, and better insulation and service life are achieved.
Patent Information
- Application Number
- CN202510168041.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-17
AI Technical Summary
When existing energy storage cables face harsh conditions such as severe cold, high temperature, torsion and bending, they lack compressive and torsion resistance, resulting in reduced insulation and short service life.
A compressive outer shield layer consisting of high-density polyethylene, low-density polyethylene, ethylene-vinyl acetate copolymer and elastic particles is used to form a compressive and torsion-resistant energy storage cable.
It significantly improves the compression, bending and torsion resistance of the cable, enhances insulation and service life, and is suitable for complex working conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage cables, and in particular to a compression-resistant and torsion-resistant energy storage cable and a preparation method thereof. Background Art
[0002] With the continuous development of society and the widespread application of electrification technology, all walks of life have higher and higher requirements for the quality and performance of wires and cables. Traditional cables have always been used only for power transmission. However, in some special fields, such as power energy storage systems, special energy storage cables are required to form connections between battery modules on the DC side of the system, between battery clusters, between battery clusters and junction boxes, or between battery clusters and energy storage converters, so as to achieve the storage and utilization of excess energy. The highest voltage level of energy storage cables is DC 1500V, and the highest continuous operating temperature of the conductor is 125℃. During use, it needs to face harsh conditions such as battery acid and alkali; severe cold; torsion; bending, and other harsh conditions, and withstand more severe tests. Therefore, the insulation materials for energy storage cables not only require conventional properties such as safety, environmental protection, halogen-free, low smoke, and good insulation, but also have higher requirements for special properties such as high flame retardancy, acid and alkali resistance, low temperature resistance, high temperature aging resistance, long life, and softness.
[0003] At present, the existing energy storage cable sheath materials are mostly polyethylene materials or polyvinyl chloride materials, but such materials are gradually exposed to poor weather resistance, easy cracking and aging in harsh working conditions such as severe cold or high temperature, which limits their application. And because wires and cables are usually round, most wires and cables will encounter the problem of being squeezed during use, which will cause the wires and cables to deform at the least, and damage the internal structure of the wires and cables at the worst, and even cause safety accidents. A shielding layer is also set on the outside of the cable core of the energy storage cable. The shielding layer can be shielded by copper tape or copper mesh. The copper mesh used as the shielding layer is a dense mesh woven in an interlaced manner, and the copper wire is thin, which is easy to break in a twisted state. When the copper tape is twisted in the winding direction, it will also tighten the cable core, causing the cable body to be stiff and difficult to bend. It is not suitable for working in working conditions that require bending or twisting.
[0004] Energy storage cables need to cope with many adverse working environments, but the existing energy storage cables do not have outstanding performance in terms of compression and torsion resistance. It is difficult to ensure the insulation and normal operation of the wires and cables under complex external forces. Even under complex torsion and bending forces, the wires and cables will be damaged and unable to work, which shortens the service life of the energy storage cables. Therefore, how to meet the compression and torsion resistance required by such cables is an urgent problem to be solved. Summary of the invention
[0005] The purpose of the present invention is to provide a compression-resistant and torsion-resistant energy storage cable and a preparation method thereof, so as to solve the following technical problems: The existing compression and torsion-resistant energy storage cables have the problems of poor compression resistance and poor torsion resistance.
[0006] The purpose of the present invention can be achieved by the following technical solutions: A compression-resistant and torsion-resistant energy storage cable comprises, from the inside to the outside, a cable core, an insulating layer, a lubricating shielding layer and a compression-resistant outer sheath, wherein the compression-resistant outer sheath comprises at least the following raw materials in parts by weight: 70-90 parts of high-density polyethylene; 10-20 parts of low-density polyethylene; 20-30 parts of elastic particles; 30-40 parts of ethylene-vinyl acetate copolymer; 30-40 parts of flame retardant; 5-10 parts of maleic anhydride grafted polyethylene propylene rubber; 0.1-1 parts of antioxidant; 1-2 parts of lubricant; 0.1-1 parts of crosslinking agent; 0.1-1 parts of auxiliary crosslinking agent; The elastic particles include at least the following raw materials in parts by weight: 100 parts of EPDM rubber / nitrile rubber composite material; 5-8 parts of zinc oxide; 1-2 parts of stearic acid; 40-50 parts of carbon black; 1-2 parts of accelerator TMTD; 2-3 parts of sulfur; and 2-4 parts of antioxidant.
[0007] As a further solution of the present invention: the preparation method of the elastic particles comprises the following steps: Adding EPDM rubber, nitrile rubber and ethylene-vinyl acetate copolymer into an internal mixer, mixing at a temperature of 140-150° C. and a rotation speed of 30-40 r / min to obtain an EPDM rubber / nitrile rubber composite material; The EPDM rubber / nitrile rubber composite material, zinc oxide, stearic acid, carbon black, accelerator TMTD, sulfur and antioxidant are added to an open mill, mixed at a temperature of 150-160° C. and a rotation speed of 40-50 r / min, and then vulcanized on a flat vulcanizer for 15-20 minutes at a pressure of 20-25 MPa to obtain elastic particles.
[0008] As a further solution of the present invention: the mass ratio of the EPDM rubber, the nitrile rubber and the ethylene-vinyl acetate copolymer in the elastic particles is 50-60:45-55:1-3.
[0009] As a further solution of the present invention: the method for preparing the material of the compression-resistant outer sheath comprises at least the following steps: Prepare raw materials according to the weight components, put all the raw materials into a high-speed mixer, mix at 80-90°C, mix for 5-10 minutes, then put the mixture into a banbury mixer for kneading at 130-170°C for 15-25 minutes to obtain a mixture; The mixed material is added into a twin-screw extruder and extruded at 100-150° C. to obtain the material for preparing the compression-resistant outer protective layer.
[0010] As a further embodiment of the present invention: the antioxidant is selected from one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, tris[2,4-di-tert-butylphenyl]phosphite, distearyl thiodipropionate, dilauryl thiodipropionate, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine or 4,4'-thiobis(6-tert-butyl-3-methylphenol), the lubricant is selected from one or more of zinc stearate, calcium stearate, magnesium stearate, polyethylene wax or ethylene bisstearamide, the flame retardant is a composite inorganic flame retardant, the crosslinking agent is selected from one of 2,5-dimethyl-2,5-di-tert-butyl peroxide or diisopropylbenzene peroxide, and the auxiliary crosslinking agent is one or more of triallyl isocyanurate and trimethylolpropane trimethacrylate.
[0011] A method for preparing a compression-resistant and torsion-resistant energy storage cable as described in any one of the above, comprising at least the following steps: An insulating layer is formed on the surface of the cable core, a lubricating shielding layer is then formed on the insulating layer, and finally a pressure-resistant outer sheath is formed on the lubricating shielding layer.
[0012] As a further solution of the present invention: the lubricating shielding layer includes a tinned braided shielding mesh and lubricating oil, and the lubricating oil is coated on the contact surface between the tinned braided shielding mesh and the insulating layer, and on the contact surface between the tinned braided shielding mesh and the pressure-resistant outer sheath.
[0013] As a further solution of the present invention: the lubricating oil at least comprises a mixture of petroleum jelly and expanded graphite, and the content of the expanded graphite in the lubricating oil is 10-20wt%.
[0014] As a further solution of the present invention: the cable core is a tinned copper wire twisted soft structure conductor, and the insulation layer is a ceramic silicone rubber insulation layer.
[0015] Beneficial effects of the present invention: The wire and cable proposed in the present invention comprises, from the inside to the outside, a cable core, an insulating layer, a lubricating shielding layer and a compressive outer sheath. The cable core and the insulating layer play the basic function of the wire and cable, that is, the basic ability to transmit information. The lubricating shielding layer plays an anti-interference function, and the compressive outer sheath plays a function of protecting the internal structure. In the present invention, a matrix resin system is formed by compounding high-density polyethylene, low-density polyethylene, ethylene-vinyl acetate copolymer and elastic particles to form a compressive outer sheath of the energy storage cable, which has excellent mechanical, physical and electrical properties, and better realizes the excellent performance of the outer sheath material of the energy storage material in terms of high temperature resistance, low temperature resistance, wear resistance, etc., and has good mechanical properties such as compression resistance, bending resistance and torsion resistance. The lubricating shielding layer provided between the compressive outer sheath and the insulating layer of the present invention has good shielding performance and lubrication performance. While satisfying the shielding function, it can also avoid torsion damage of the shielding net, thereby improving the torsion resistance of the cable. The energy storage cable of the present invention can be applied to working environments under complex torsion, pressure and bending forces, and can meet the bending performance and torsion performance of the energy storage cable. EPDM rubber is the main component, which ensures the cable material is soft, resistant to high and low temperatures, ozone and aging.
[0016] The compression-resistant outer protective layer prepared by the present invention uses high-density polyethylene as the main resin, which improves the strength of the material, adds a small amount of low-density polyethylene to increase the toughness of the material, and also adds ethylene-vinyl acetate copolymer and elastic particles to increase the compression resistance of the material. Among them, the elastic particles are a composite material of ethylene propylene rubber and nitrile rubber, so that the prepared compression-resistant outer protective layer has good compression strength under low or high temperature environments, and ethylene-vinyl acetate copolymer is added during the preparation of the elastic particles to improve the compatibility of the two rubber particles and further improve the mechanical properties of the elastic particles. The present invention combines high-density polyethylene, low-density polyethylene and rubber-based elastic particles, which can give the matrix good compression resistance, softness and weather resistance, but the compatibility and processing performance of the two are poor. The present invention further adds maleic anhydride-grafted ethylene propylene rubber in the matrix system, which can improve the compatibility between the components of the substrate and promote the improvement of material toughness and strength.
[0017] The lubricating shielding layer prepared by the present invention applies lubricating oil to the contact surface between the tin-plated braided shielding net and the insulating layer, and the contact surface with the compression-resistant outer sheath. The lubricating oil is a mixture of petroleum jelly and expanded graphite. The petroleum jelly is lubricating, and can reduce the friction between the shielding layer and the insulating layer, and between the shielding layer and the compression-resistant outer sheath, thereby improving the anti-torsion performance of the cable, solving the problem that the tin-plated braided shielding net is easy to break under the torsion of the cable, and ensuring that the shielding layer can guarantee a long service life under the working conditions of frequent torsion and stretching, and the expanded graphite in the lubricating oil can further improve the flame retardant performance of the prepared energy storage cable. The elastic particles added in the compression-resistant outer sheath prepared in the present invention also have certain oil resistance, avoid the overflow of lubricating oil to a certain extent, and improve the service life of the prepared energy storage cable. DETAILED DESCRIPTION
[0018] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Example 1 The method for preparing lubricating oil comprises the following steps: 10 parts by mass of petroleum jelly and 1.5 parts by mass of expanded graphite were mixed to obtain lubricating oil.
[0020] Example 2 The method for preparing elastic particles comprises the following steps: 50 parts by weight of ethylene propylene diene monomer rubber (EPDM 4045), 50 parts by weight of nitrile rubber (NBR 2707) and 1 part by weight of ethylene vinyl acetate copolymer (EVA 14 / 5) were added into an internal mixer, and mixed at a temperature of 140° C. and a rotation speed of 30 r / min to obtain an EPDM rubber / nitrile rubber composite material; The prepared EPDM rubber / nitrile rubber composite material, 6 parts by mass of zinc oxide, 1 part by mass of stearic acid, 40 parts by mass of carbon black, 1 part by mass of accelerator TMTD, 2 parts by mass of sulfur and 2 parts by mass of antioxidant were added to an open mill, mixed at a temperature of 150°C and a rotation speed of 40 r / min, and then vulcanized on a flat vulcanizer at a pressure of 25 MPa for 15 minutes to obtain elastic particles.
[0021] Example 3 The preparation method of elastic particles comprises the following steps: 60 parts by weight of ethylene propylene diene monomer rubber (EPDM 4045), 50 parts by weight of nitrile rubber (NBR 2707) and 2 parts by weight of ethylene vinyl acetate copolymer (EVA 14 / 5) were added into an internal mixer, and mixed at a temperature of 140° C. and a rotation speed of 30 r / min to obtain an EPDM rubber / nitrile rubber composite material; The prepared EPDM rubber / nitrile rubber composite material, 6 parts by mass of zinc oxide, 2 parts by mass of stearic acid, 40 parts by mass of carbon black, 1 part by mass of accelerator TMTD, 2 parts by mass of sulfur and 2 parts by mass of antioxidant were added to an open mill, mixed at a temperature of 150°C and a rotation speed of 40 r / min, and then vulcanized on a flat vulcanizer at a pressure of 25 MPa for 15 minutes to obtain elastic particles.
[0022] Example 4 The method for preparing the material of the compression-resistant outer sheath comprises the following steps: 70 parts by weight of high-density polyethylene (HDPE 5000S), 10 parts by weight of low-density polyethylene (HDPE 1F-7B), 10 parts by weight of the elastic particles prepared in Example 2, 30 parts by weight of ethylene-vinyl acetate copolymer (EVA 14 / 5), 30 parts by weight of montmorillonite / aluminum hydroxide composite inorganic flame retardant, 5 parts by weight of maleic anhydride grafted polyethylene propylene rubber, 0.5 parts by weight of antioxidant dilauryl thiodipropionate, 1 part by weight of lubricant calcium stearate, 0.5 parts by weight of crosslinking agent diisopropylbenzene peroxide and 0.2 parts by weight of auxiliary crosslinking agent triallyl isocyanurate were put into a high-speed mixer at a mixing temperature of 90° C. and a mixing time of 5 min, and then the mixture was put into a banbury mixer for mixing at a banbury temperature of 150° C. and a banbury time of 15 min to obtain a mixture; The mixed material is added into a twin-screw extruder and extruded at 100-150° C. to obtain the material for preparing the compression-resistant outer protective layer.
[0023] The preparation method of the compression-resistant and torsion-resistant energy storage cable comprises the following steps: The ceramic silicone rubber insulation layer is formed as an insulation layer on the surface of the cable core; The lubricating oil prepared in Example 1 is applied on both sides of the tinned braided shielding mesh to form a lubricating shielding layer on the surface of the insulating layer; The material of the compression-resistant outer sheath prepared in this embodiment is then applied on the surface of the lubricating shielding layer to form a compression-resistant outer sheath, thereby obtaining a compression-resistant and torsion-resistant energy storage cable.
[0024] Example 5 The method for preparing the material of the compression-resistant outer sheath comprises the following steps: 70 parts by weight of high-density polyethylene (HDPE 5000S), 10 parts by weight of low-density polyethylene (HDPE 1F-7B), 10 parts by weight of elastic particles prepared in Example 3, 30 parts by weight of ethylene-vinyl acetate copolymer (EVA 14 / 5), 30 parts by weight of montmorillonite / aluminum hydroxide composite inorganic flame retardant, 5 parts by weight of maleic anhydride grafted polyethylene propylene rubber, 0.5 parts by weight of antioxidant dilauryl thiodipropionate, 1 part by weight of lubricant calcium stearate, 0.5 parts by weight of crosslinking agent diisopropylbenzene peroxide and 0.2 parts by weight of auxiliary crosslinking agent triallyl isocyanurate were put into a high-speed mixer at a mixing temperature of 90° C. and a mixing time of 5 min, and then the mixture was put into a banbury mixer for mixing at a banbury temperature of 150° C. and a banbury time of 15 min to obtain a mixture; The mixed material is added into a twin-screw extruder and extruded at 100-150° C. to obtain the material for preparing the compression-resistant outer protective layer.
[0025] In the preparation steps of the compression-resistant and torsion-resistant energy storage cable, compared with Example 4, this example only replaces the mass of the compression-resistant outer sheath material prepared in Example 4 added in Example 4 with the compression-resistant outer sheath material prepared in this example, and the remaining components and preparation method are exactly the same as Example 4.
[0026] Example 6 The method for preparing the material of the compression-resistant outer protective layer comprises the following steps: 80 parts by weight of high-density polyethylene (HDPE 5000S), 15 parts by weight of low-density polyethylene (HDPE 1F-7B), 20 parts by weight of elastic particles prepared in Example 2, 35 parts by weight of ethylene-vinyl acetate copolymer (EVA 14 / 5), 30 parts by weight of montmorillonite / aluminum hydroxide composite inorganic flame retardant, 8 parts by weight of maleic anhydride grafted polyethylene propylene rubber, 0.5 parts by weight of antioxidant dilauryl thiodipropionate, 1 part by weight of lubricant calcium stearate, 0.5 parts by weight of crosslinking agent diisopropylbenzene peroxide and 0.2 parts by weight of auxiliary crosslinking agent triallyl isocyanurate were put into a high-speed mixer at a mixing temperature of 90° C. and a mixing time of 5 min, and then the mixture was put into a banbury mixer for mixing at a banbury temperature of 150° C. and a banbury time of 15 min to obtain a mixture; The mixed material is added into a twin-screw extruder and extruded at 100-150° C. to obtain the material for preparing the compression-resistant outer protective layer.
[0027] In the preparation steps of the compression-resistant and torsion-resistant energy storage cable, compared with Example 4, this example only replaces the mass of the compression-resistant outer sheath material prepared in Example 4 added in Example 4 with the compression-resistant outer sheath material prepared in this example, and the remaining components and preparation method are exactly the same as Example 4.
[0028] Example 7 The method for preparing the material of the compression-resistant outer protective layer comprises the following steps: 80 parts by weight of high-density polyethylene (HDPE 5000S), 15 parts by weight of low-density polyethylene (HDPE 1F-7B), 20 parts by weight of elastic particles prepared in Example 3, 35 parts by weight of ethylene-vinyl acetate copolymer (EVA 14 / 5), 30 parts by weight of montmorillonite / aluminum hydroxide composite inorganic flame retardant, 8 parts by weight of maleic anhydride grafted polyethylene propylene rubber, 0.5 parts by weight of antioxidant dilauryl thiodipropionate, 1 part by weight of lubricant calcium stearate, 0.5 parts by weight of crosslinking agent diisopropylbenzene peroxide and 0.2 parts by weight of auxiliary crosslinking agent triallyl isocyanurate were put into a high-speed mixer at a mixing temperature of 90° C. and a mixing time of 5 min, and then the mixture was put into a banbury mixer for mixing at a banbury temperature of 150° C. and a banbury time of 15 min to obtain a mixture; The mixed material is added into a twin-screw extruder and extruded at 100-150° C. to obtain the material for preparing the compression-resistant outer protective layer.
[0029] In the preparation steps of the compression-resistant and torsion-resistant energy storage cable, compared with Example 4, this example only replaces the mass of the compression-resistant outer sheath material prepared in Example 4 added in Example 4 with the compression-resistant outer sheath material prepared in this example, and the remaining components and preparation method are exactly the same as Example 4.
[0030] Comparative Example 1 The preparation method of the compression-resistant and torsion-resistant energy storage cable comprises the following steps: The ceramic silicone rubber insulation layer is formed as an insulation layer on the surface of the cable core; A tinned braided shielding mesh not coated with lubricating oil is placed on the surface of the insulating layer to form a shielding layer; The material of the compression-resistant outer sheath prepared in Example 2 is then used to form a compression-resistant outer sheath on the surface of the shielding layer to obtain a compression-resistant and torsion-resistant energy storage cable.
[0031] Comparative Example 2 The preparation method of the compression-resistant and torsion-resistant energy storage cable comprises the following steps: In the preparation step of the compression-resistant outer sheath material, compared with Example 4, this comparative example only does not add elastic particles, and the remaining components and preparation method are completely consistent with Example 4.
[0032] In the preparation steps of the compression-resistant and torsion-resistant energy storage cable, compared with Example 4, this comparative example only replaces the mass of the compression-resistant outer sheath material prepared in Example 4 added in Example 4 with the compression-resistant outer sheath material prepared in this comparative example, and the remaining components and preparation method are exactly the same as those in Example 4.
[0033] Comparative Example 3 In the preparation steps of the compression-resistant and torsion-resistant energy storage cable, compared with Comparative Example 2, the tinned braided shielding mesh formed in this comparative example is not coated with lubricating oil, and the remaining components and preparation method are completely consistent with Comparative Example 2.
[0034] Performance Testing Torsion resistance test: The cable samples of Examples 4-7 and Comparative Examples 1-3 should be tested at an ambient temperature of 20°C ± 1°C. The cable sample is first twisted 1080° clockwise, then restored to the natural state, then twisted 1080° counterclockwise, and then restored to the natural state. This is a cycle, and a total of 5000 cycles of tests are carried out. The twisting speed is 720° / min-1080° / min. During this period, a thermal cycle test of 8h power-on heating and 16h natural cooling is carried out. During the power-on period, the conductor should be stabilized at the operating temperature of the cable at 90℃. The power-on and cooling process should run through the entire test process. After completing the tests specified in the above test procedures, the surface of the sample should be visually observed to have no cracks and distortion, no breakdown in the 5min AC withstand voltage test under 3.5U0 (U0 represents the rated power frequency voltage between the conductor designed for the cable and the ground or the metal shield), and the partial discharge under 1.73U0 voltage should be no more than 10pA·s. After all tests are completed, the cable is dissected to determine whether there are cracks in various parts of the cable; the test results are shown in Table 1; Mechanical strength test: The cable environmental stress cracking (ESCR) test described in GB / T 2951-2008 "General test methods for insulation and sheath materials of electric and optical cables" was used to test the mechanical strength of the cable samples of Examples 4-7 and Comparative Examples 1-3, and the test results were tabulated; see Table 1; The compression performance test was carried out according to GB / T 2951-2008 to test the permanent deformation rate and deformation rate under load of the cable samples obtained in Examples 3-6 and Comparative Examples 1-3; the test results are shown in Table 1; Table 1: Statistical table of performance test data of test pieces of Examples 4-7 and Comparative Examples 1-3
[0035] It can be seen from Table 1 that the compression-resistant and torsion-resistant energy storage cable prepared in the present application has good mechanical strength, compression resistance and torsion resistance. In Comparative Example 1, lubricating oil is not applied on the tinned braided shielding net, and the energy storage cable obtained has partial rupture inside the cable in the torsion resistance test. In Comparative Example 2, elastic particles are not added to the compression-resistant outer sheath prepared, and the permanent deformation rate and deformation rate under load of the energy storage cable obtained are increased, and the compression resistance is reduced. In Comparative Example 3, neither the shielding layer nor the outer sheath is modified, and the compression resistance and torsion resistance of the obtained energy storage cable are not improved.
[0036] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A compression and torsion resistant energy storage cable, characterized in that: From the inside to the outside, it includes a cable core, an insulating layer, a lubricating shielding layer and a pressure-resistant outer sheath, and the pressure-resistant outer sheath includes at least the following raw materials in parts by weight: 70-90 parts of high-density polyethylene; 10-20 parts of low-density polyethylene; 20-30 parts of elastic particles; 30-40 parts of ethylene-vinyl acetate copolymer; 30-40 parts of flame retardant; 5-10 parts of maleic anhydride grafted polyethylene propylene rubber; 0.1-1 parts of antioxidant; 1-2 parts of lubricant; 0.1-1 parts of crosslinking agent; 0.1-1 parts of auxiliary crosslinking agent; The elastic particles include at least the following raw materials in parts by weight: 100 parts of EPDM rubber / nitrile rubber composite material; 5-8 parts of zinc oxide; 1-2 parts of stearic acid; 40-50 parts of carbon black; 1-2 parts of accelerator TMTD; 2-3 parts of sulfur; and 2-4 parts of antioxidant.
2. The compression-resistant and torsion-resistant energy storage cable according to claim 1 is characterized in that: The method for preparing the elastic particles comprises the following steps: Adding EPDM rubber, nitrile rubber and ethylene-vinyl acetate copolymer into an internal mixer, mixing at a temperature of 140-150° C. and a rotation speed of 30-40 r / min to obtain an EPDM rubber / nitrile rubber composite material; The EPDM rubber / nitrile rubber composite material, zinc oxide, stearic acid, carbon black, accelerator TMTD, sulfur and antioxidant are added to an open mill, mixed at a temperature of 150-160° C. and a rotation speed of 40-50 r / min, and then vulcanized on a flat vulcanizer for 15-20 minutes at a pressure of 20-25 MPa to obtain elastic particles.
3. The compression-resistant and torsion-resistant energy storage cable according to claim 2 is characterized in that: The mass ratio of the EPDM rubber, the nitrile rubber and the ethylene-vinyl acetate copolymer in the elastic particles is 50-60:45-55:1-3.
4. The compression-resistant and torsion-resistant energy storage cable according to claim 1, characterized in that: The method for preparing the material of the compression-resistant outer sheath comprises at least the following steps: Prepare raw materials according to the weight components, put all the raw materials into a high-speed mixer, mix at 80-90°C, mix for 5-10 minutes, then put the mixture into a banbury mixer for kneading at 130-170°C for 15-25 minutes to obtain a mixture; The mixed material is added into a twin-screw extruder and extruded at 100-150° C. to obtain the material for preparing the compression-resistant outer protective layer.
5. The compression-resistant and torsion-resistant energy storage cable according to claim 4 is characterized in that: The antioxidant is selected from one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, tris[2,4-di-tert-butylphenyl]phosphite, distearyl thiodipropionate, dilauryl thiodipropionate, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine or 4,4'-thiobis(6-tert-butyl-3-methylphenol), the lubricant is selected from one or more of zinc stearate, calcium stearate, magnesium stearate, polyethylene wax or ethylene bisstearamide, the flame retardant is a composite inorganic flame retardant, the crosslinking agent is selected from one of 2,5-dimethyl-2,5-di-tert-butyl peroxide or diisopropylbenzene peroxide, and the auxiliary crosslinking agent is one or a mixture of triallyl isocyanurate and trimethylolpropane trimethacrylate.
6. A method for preparing a compression-resistant and torsion-resistant energy storage cable according to any one of claims 1 to 5, characterized in that: At least the following steps are included: An insulating layer is formed on the surface of the cable core, a lubricating shielding layer is then formed on the insulating layer, and finally a pressure-resistant outer sheath is formed on the lubricating shielding layer.
7. The method for preparing the compression-resistant and torsion-resistant energy storage cable according to claim 6, characterized in that: The lubricating shielding layer comprises a tinned braided shielding mesh and lubricating oil, and the lubricating oil is coated on the contact surface between the tinned braided shielding mesh and the insulating layer, and on the contact surface between the tinned braided shielding mesh and the pressure-resistant outer sheath.
8. The method for preparing the compression-resistant and torsion-resistant energy storage cable according to claim 7, characterized in that: The lubricating oil at least comprises a mixture of petroleum jelly and expanded graphite, and the content of the expanded graphite in the lubricating oil is 10-20wt%.
9. The method for preparing a compression-resistant and torsion-resistant energy storage cable according to claim 6, characterized in that: The cable core is a tinned copper wire twisted soft structure conductor, and the insulating layer is a ceramic silicone rubber insulating layer.
Citation Information
Patent Citations
1E-grade K1-type low-smoke halogen-free vulcanized crosslinked cable shield material for AP1000 nuclear power station and preparation method of cable shield material
CN103030873A
Halogen-free flame retardant thermoplastic polyolefin cable material
CN103265752A
Preparation method of thermal conductive electrical insulating material
CN105061855A
Waterproof and fireproof electric cable
CN105913931A
Sheath rubber material for energy storage battery connecting cable and preparation method of sheath rubber material
CN114874606A
Cited By
Preparation method of high-flexibility torsion-resistant drag chain cable
CN120737473A
Preparation method of high-flexible and high-torsion-resistant drag chain cable
CN120737473B